Effects of Synthetic Acaricides and Nosema ceranae (Microsporidia: Nosematidae) on Molecules Associated with Chemical Communication and Recognition in Honey Bees - Porrini, Martín Pablo (2020)
Acaricides and the gut parasite Nosema ceranae are commonly present in most productivehives. Those stressors could be affecting key semiochemicals, which act as homeostasis regulators inApis mellifera colonies, such as cuticular hydrocarbons (CHC) involved in social recognition and ethyloleate (EO) which plays a role as primer pheromone in honey bees. Here we test the effect of amitraz,coumaphos, tau-fluvalinate and flumethrin, commonly applied to treat varroosis, on honey beesurvival time, rate of food consumption, CHC profiles and EO production on N. ceranae-infected andnon-infected honey bees. Different sublethal concentrations of amitraz, coumaphos, tau-fluvalinate andflumethrin were administered chronically in a syrup-based diet. After treatment, purified hole-bodyextracts were analyzed by gas chromatography coupled to mass spectrometry. While N. ceranaeinfection was also shown to decrease EO production affecting survival rates, acaricides showed nosignificant effect on this pheromone. As for the CHC, we found no changes in relation to the healthstatus or consumption of acaricides. This absence of alteration in EO or CHC as response to acaricidesingestion or in combination with N. ceranae, suggests that worker honey bees exposed to those highlyubiquitous drugs are hardly differentiated by nest-mates. Having determined a synergic effect onmortality in worker bees exposed to coumaphos and Nosema infection but also, alterations in EOproduction as a response to N. ceranae infection it is an interesting clue to deeper understand theeffects of parasite-host-pesticide interaction on colony functioning.